KEPASTIAN HUKUM BAGI PENANAM MODAL ASING SEHUBUNGAN DENGAN INKONSTITUSIONAL UNDANG-UNDANG CIPTA KERJA - Ferdinand Jason; David Tan (LPPM Universitas Ekasakti Padang, 2022)
Foreign Investment or commonly referred to as PMA is an investment activity carried out by foreign investors with the aim of being able to expand business or business in a country territory. In this case, the Indonesian government is trying to improve the investment climate in Indonesia by presenting the Job Creation Law. The existence of the Employment Creation Law has created a number of contradictions with the laws and regulations. This normative juridical research will discuss legal certainty for foreign investment in relation to the constitutional work creation law. This study aims to determine the basis and reasons for the formal examination of the Job Creation Act in the Constitutional Court, as well as to determine legal certainty for PMA. The results of the study indicate that legal certainty for PMA is currently a problem, so that the government plays an important role in making policies that do not harm the parties.